Hypothalamic prolylcarboxypeptidase (PRCP) in the regulation of melanocortin system - Diano, Sabrina (Henry Stewart Talks, 2010)
The hypothalamus, POMC, Congenics mapping, PRCP, alpha-MSH peptide sequence, Effect of alpha-MSH on food intake, Generation of PRCP gene-trap mice, Prcpgt/gt mice are leaner and resistant to diet-induced obesity, Effect of PRCP inhibitors on food intake, PRCP mRNA is increased in the hypothalamus of Dio mice